Accounting Treatment of Zakat at the National Zakat Agency (Baznas) of Nunukan Regency - Fadli, Zahri; Astika, Sri; Herlina, Herlina; Harianti, Harianti (INVOICE : JURNAL ILMU AKUNTANSI, 2025)
This study aims to evaluate the accounting treatment of zakat at the National Zakat Agency (BAZNAS) of Nunukan Regency in accordance with the implementation of PSAK 109. Using a qualitative descriptive method with a comparative analysis approach, the study finds that BAZNAS Nunukan generally complies with PSAK 109 in terms of recognition, measurement, presentation, disclosure, and financial reporting. Zakat income and expenditure are recognized on a cash basis, aligning with PSAK 109 provisions. Although the agency has not yet received non-cash zakat assets, it applies prevailing market prices for valuation purposes. The agency demonstrates transparency in disclosing the distribution of zakat, infaq, and sadaqah (ZIS) funds, and its financial reports include a statement of financial position, statement of changes in funds, cash flow statement, and notes to the financial statements. However, challenges remain in fully optimizing the efficiency and transparency of zakat management. This study highlights the importance of standardized accounting practices to improve accountability in zakat institutions. Future research is recommended to explore the integration of digital technologies in zakat financial management systems. This study contributes to the development of Islamic financial reporting by reinforcing the relevance of PSAK 109 in enhancing institutional governance and stakeholder trust.